Vestibular neuromodulation in neurology and psychiatry - A. G. Naryshkin; I. V. Galanin; V. L. Kozlovskii; V. Yu. Popov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Te paper overviews the state of the art in one of the most rapidly developing areas of treatment of various drug-resistant diseases of the central nervous system. Diﬀerent methods of vestibular neuromodulation and their comparative efcacy in the treatment of mental and neurological disorders are described. All those methods are based on neuroplasticity activation by means of application of physical, electrical or chemical stimuli on the peripheral part of the vestibular system, which leads to the restructuring of neural connections in the brainstem and in the midbrain.